Algengi minni háttar geðkvilla og ávísana á geðdeyfðarlyf og róandi lyf í Reykjavík - Tómas Helgason; Júlíus Björnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) In 1984 an attempt was made at estimating the prevalence of minor mental illness by giving the General Health Questionnaire (GHQ) to a random sample of the population aged 20-59 years. During the same year all prescriptions for psychotropic drugs paid during one month by the Sick Benefit Association in Reykjavik were analysed. According to the GHQ survey the estimated prevalence of minor mental disorders is 13% among men and 18% among women. The prevalence is highest among those aged 20-29 years, 21%, but lowest among the 50-59 years old, 11%. The prevalence of those receiving tranquillizers during the month was 3.6% and 0.7% for those receiving antidepressants, the female/male proportion being greater than that for the prevalence of minor mental disorders. Too many patients were prescribed tranquillizers relative to those prescribed antidepressants as compared to the proportion of depressive disorders in the overall prevalence of mental disorders. In the age group 20-29 years only 0.8% were prescribed tranquillizers and 0.3% antidepressants. Compared to the prevalence of mental disorders in this age group prescriptions for psychotropic drugs are rare. It is possible that too many in the older age groups obtain prescriptions for tranquillizers, but compared to the prevalence figures it is not excessive. Á árinu 1984 var gerð rannsókn á algengi geðkvilla með skimprófi, sem lagt var fyrir 3,7% slembiúrtak fólks á aldrinum 20-59 ára. Það sama ár voru rannsakaðar geðlyfjaávísanir sem Sjúkrasamlag Reykjavíkur greiddi á einum mánuði (1, 2). Samkvæmt skimprófinu er áætlað að algengi geðkvilla fyrir utan nokkuð af áfengissýki og alvarlega geðveiki hafi verið 13% hjá körlum og 18% hjá konum í Reykjavik á aldrinum 20-59 ára, hæst hjá fólki á aldrinum 20-29 ára 21%, en lægst hjá þeim sem voru 50-59 ára 11%. Fjöldi þeirra sem fengu ávísun á róandi lyf eða geðdeyfðarlyf í einum mánuði reyndist 3,6% og 0,7%. ...